Pengaruh Mode Pembelajaran Inquiry Cooperation Berbantuan Geogebra terhadap Kemampuan Berpikir Kritis Siswa - Maisarah, Leila; Hasibuan, Lily Rohanita; Harahap, Amin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the effect of implementing the Inquiry Cooperation assisted by GeoGebra software on students’ mathematical critical thinking skills. This research employed a quantitative approach using a quasi-experimental method with a pretest–posttest control group design. The sample consisted of 60 students who were divided into an experimental group and a control group. The research instrument was a multiple-choice test consisting of 15 items that had met the criteria of validity and reliability. Data were analyzed using both descriptive and inferential statistics, including normality tests, homogeneity tests, paired sample t-tests, independent sample t-tests, and N-Gain analysis. The results showed that the average score of students’ mathematical critical thinking skills in the experimental group increased from 6.60 to 7.67, while the control group showed only a minimal improvement. The independent sample t-test yielded a significance value of 0.006 (< 0.05), indicating a significant difference between the two groups. Furthermore, the experimental group achieved an N-Gain score of 56.26% (moderately effective category), whereas the control group obtained 15.20% (ineffective category). Therefore, it can be concluded that the implementation of the Inquiry Cooperation Model assisted by GeoGebra has a positive and more. Keywords: Mathematical Critical Thinking, GeoGebra, Inquiry Cooperation Model.